Changing clinical patterns in rheumatoid arthritis management over two decades: sequential observational studies. Issue 1 (December 2016) - Mian, Aneela; Ibrahim, Fowzia; Scott, Ian; Bahadur, Sardar; Filkova, Maria; Pollard, Louise; Steer, Sophia; Kingsley, Gabrielle; Scott, David; Galloway, James
Abstract Background Rheumatoid arthritis (RA) treatment paradigms have shifted over the last two decades. There has been increasing emphasis on combination disease modifying anti-rheumatic drug (DMARD) therapy, newer biologic therapies have become available and there is a greater focus on achieving remission. We have evaluated the impact of treatment changes on disease activity scores for 28 joints (DAS28) and disability measured by the health assessment questionnaire scores (HAQ). Methods Four cross-sectional surveys between 1996 and 2014 in two adjacent secondary care rheumatology departments in London evaluated changes in drug therapy, DAS28 and its component parts and HAQ scores (in three surveys). Descriptive statistics used means and standard deviations (SD) or medians and interquartile ranges (IQR) to summarise changes. Spearman's correlations assessed relationships between assessments. Results 1324 patients were studied. Gender ratios, age and mean disease duration were similar across all cohorts. There were temporal increases in the use of any DMARDs (rising from 61 % to 87 % of patients from 1996-2014), combination DMARDs (1 % to 41 %) and biologic (0 to 32 %). Mean DAS28 fell (5.2 to 3.7), active disease (DAS28 > 5.1) declined (50 % to 18 %) and DAS28 remission (DAS28 < 2.6) increased (8 % to 28 %). In contrast HAQ scores were unchanged (1.30 to 1.32) and correlations between DAS28 and HAQ weakened (Spearman's rho fell from 0.56 to 0.44). Conclusions Treatment intensity has increased over time, disease activity has fallen and there are more remissions. However, these improvements in controlling synovitis have not resulted in comparable reductions in disability measured by HAQ. As a consequence the relationship between DAS28 and HAQ has become weaker over time. Although the reasons for this divergence between disease activity and disability are uncertain, focussing treatment entirely in suppressing synovitis may be insufficient.